2021
DOI: 10.3390/logistics5010016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E-Procurement Adoption on Company Performance: Evidence from Indonesian Manufacturing Industry

Abstract: This study was conducted to determine the performance impact of e-procurement adoption in Indonesian manufacturing companies. This study consists of four variables: top management support, information quality, implementation of e-procurement, and company performance. Pilot testing questionnaires were used to test whether the respondents understood the questions given by the researcher. After conducting the pilot test, the final questionnaire was distributed to respondents. The pilot test results and the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Based on the three parameters of the fit model analyzed, it can be concluded that the model has shown a good fit. Similar findings with Masudin et al, ( 2021a , 2021b ) research examined the effect of traceability on humanitarian logistics performance. The research obtained an SRMS value of 0.081, NFI of 92.3%, and RMS_theta of 0.099, which indicates the right model.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Based on the three parameters of the fit model analyzed, it can be concluded that the model has shown a good fit. Similar findings with Masudin et al, ( 2021a , 2021b ) research examined the effect of traceability on humanitarian logistics performance. The research obtained an SRMS value of 0.081, NFI of 92.3%, and RMS_theta of 0.099, which indicates the right model.…”
Section: Resultssupporting
confidence: 84%
“…Those values defined more than half of the total explanation required. Masudin and et al, ( 2021a , 2021b ), in their research on the humanitarian logistics performance variable, obtained an R-square value of 57.3%, which also only defined half of the overall explanation for the variable.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes in processes and organisational structure and policies and strategies to implement transparency should also be brought together. Senior management support is crucial in fostering a supportive environment and providing businesses with resources (Masudin et al, 2021). The previous study had shown that transparency provides a beneficial influence on a company's performance (Zhu et al, 2018).…”
Section: Managerial Role and Transparencymentioning
confidence: 99%
“…1) e-Procurement and e-GP Vision E-procurement [9] [10] uses secure web-based application platforms by the government as a buyer to communicate with the bidder's community in a paperless environment free from inconveniences, delays, and physical insecurities of any kind. According to the definition, e-procurement involves the procurement of goods and services using the internet or electronic network in its implementation [11]. CPTU made the e-GP vision to enhance the efficiency and transparency of the Bangladesh public procurement system [1].…”
Section: Literature Reviewmentioning
confidence: 99%